PENGUKURAN NILAI KONDISI TERNAK (NKT), CONCEPTION RATE (CR), SERVICE PER CONCEPTION (S/C) PADA SAPI CROSSBREED LIMOUSIN DI KECAMATAN BALONGPANGGANG KABUPATEN GRESIK - Septian H, Fajar; Mustofa, Imam; Sektiari L., Bambang (Ovozoa: Journal of Animal Reproduction, 2019)
This research was conducted to find out the Body Condition Score (BCS, in nine scale) of 30 Limousine crossbred cows in Balongpanggang, Gresik regency at the time of  Artificial Insemination,  21 and 60 days later. Questionnaires obtained to identify the knowledge of farmers and inseminators in estrous detection. Conception Rate (CR) and Service per Conception (S/C) counted based on pregnancy diagnosis through rectal palpation 60 days post insemination. The result showed that the average of BCS in pregnant cows at 60 days post insemination was highest compared to the others. Conception rate and service per conception of the cows were 60% and 1.63 respectively, meanwhile the knowledge of estrous detection of farmers was lower compared to those of inseminator. It could be concluded that implementation of AI technique in Limousine crossbred cows at Balongpanggang, Gresik regency was good enough, but the knowledge of farmers about estrous detection needs to be improved.